Digital economy: A paradise or threat in the new norm? - Beh, Loo See (2019)
The digital economy is exponentially expanding into every aspect of our lives and industries with sensors, mobile, cloud and big data. This work-in-progress paper will be discussed in 2 parts. Part One will examine the digital firms, fintechs that leverage their capability and large customer base in the digital financial services that include Grab and GoJek and the associated services of digital wallets in Malaysia and neighbouring countries who are “enablers” in the digital economy or “disrupters” in a conventional economy with the growing pool of tech-savvy consumers and rising tide of digital economy and underpinning consumption. In Part Two, can the digital economy protect the safety, security and privacy of its customers and citizenry? Herein lies the problem – disruptive digital technology, cyberattacks, compromising data breach committed by hackers and fraudsters that could lead to cybercriminals and associated activities of identity theft and so forth. How does the government keep pace with the rapid change and continuing digital disruption in compliance within the legal requirement as innovation is exponentially experienced? This paper will illustrate the security condition of the digital economy risks and the preparedness in facing them as both business and personal risks in Malaysia and global comparison, wherein possible, including existing policies in reinforcing defense in the new norm.